(untitled) (Journal of Engineering, 2012)
Optimum allocation of water for restoration of Iraqi marshes is essential for different related authorities. Abo-Ziriq marsh area about 120 km2 is situated 40 km east of Al-Nassryia city. After comparing the measured annual water qualities with the Iraqi standards for surface water quality evaluation, Abo-Ziriq marsh water quality was in acceptable limit. Hydro balance computation were done for each month by using interface among the HEC-RAS, HEC-GeoRAS and ArcView GIS software and built a number of eco-hydro relationships to simulate the marsh ecosystem by using HEC-EFM program to estimate water allocation adequate for ecosystem requirement and constructs a GIS hydraulic reference map to show inundation area, depth grid and velocity distribution, the optimal flow result consists of three different scenarios (24, 30.3 and 33.6 m3 /s) for marsh operation during the year. A computer program in MATLAB 7 was developed to simulate the optimization model to determine the optimum flow value entry to lower zone. The priority of each parameter is represented by a weight associated with each of them (penalty factor). The model was used for different scheme of penalty factor value and examines three cases of flow (wet, moderate and dry years). The results obtained from the program run show that the optimum flow values are not affected significantly with changing the scheme of the penalty factors. Hence, any set of solutions can be use for operation the control structure of two inlets in the lower zone that best fits the objective of the system and increase flow release from Abo Jiry inlet to minimum deviation in water quality during the most time of the year